Functionalization of 5-hydroxyindole-based i-melanin pigment for hair dyeing and UV-protective applications - Yeo, Chan Seo; Choi, Jongyun; Kim, Hee Jung; Chung, Joo Hee; Park, Hyun A.; Seo, Jong Bok; Jung, Ji Chul; Jung, Wonjong; Choi, Kwon Young (Progress in Organic Coatings, 2025)
In this study, 5-hydroxyindole-based i-melanin was biosynthesized through enzymatic reactions catalyzed by flavin monooxygenase (FMO) and sequential MelC tyrosinase. The monomer underwent intracellular random polymerization, resulting in a novel symmetric melanin. The synthesized i-melanin exhibited a significantly darker black coloration compared to conventional melanin and demonstrated enhanced biological activities, including antioxidant and antibacterial properties. The physical and biological characteristics of i-melanin were analyzed using UV/Vis spectroscopy, ABTS assays, and growth inhibition studies. Notably, i-melanin displayed antifungal activity against Candida albicans. For functional applications, i-melanin was formulated as a hair dye and incorporated into a UV-protection cream through complexation with ZnO. Both formulations exhibited excellent dyeing efficacy and UV-blocking performance. Given the high production yield of i-melanin, its scalability for industrial applications appears promising. These findings suggest that this novel melanin has potential for integration into various functional products in the future.
Keywords: 5-Hydroxyindole; Antifungal activities; Enzymatic reaction; Functionalizations; Hair dyeings; I-melanin; Melanin coating; Melanin pigments; Reaction catalyzed; UV protective; Antifungal activity; Hair dyeing; I-melanin; Melanin coating; UV protective